Biochemical Profile of Malnutrition Children at a Tertiary Care Hospital - Nasir Ayaz, Zahid Ullah, Arshad Karim (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Children’s malnutrition is a major public health problem around the world. More than 41% of the deaths of children between the ages of six and 24 months in underdeveloped nations each year are attributable to it, which amounts to 2.3 million deaths. In our study, we’ll examine the biochemical markers and nutritional indicators of these children when they first arrive. Aim: To determine the biochemical profile of children with SAM presenting to Lady Reading Hospital, Peshawar. Methods: A descriptive cross-sectional study was conducted in the Department of Pediatrics at Lady Reading Hospital in Peshawar, Pakistan. Pakistan is the home of the hospital. A total of 161 patients were assessed during this inquiry. Everyone’s age, gender, gestation, delivery type (including cesarean section), and weight at birth have been recorded and accounted for. At the time of each child’s admittance, their biochemical state (including their serum electrolytes, serum albumin, and hemoglobin level), as well as their age, gender, and weight for their age, were all taken into consideration. In the biochemical profile, low sodium (135mmol/l), low potassium (3.5mmol/l), low cholesterol (95), low albumin (35g/l), low calcium (2.2mmol/l), and low sugar (3mmol/l) were present, along with anemia (hemoglobin levels of 13 g/dl for males and 12g/dl for women). The mother’s age, level of education, and location in the world were documented. Results: In this study mean age was 3 years with SD±2.71. Thirty eight children were male and 62% children were female. Biochemical profile of 161 children with severe acute malnutrition was analyzed as hyponatremia was 23(14%) hypokalemia was 109(68%), hypochloremia was 26(16%), hypoalbuminemia was 11(7%), hypocalcemia was 56(35%), hypoglycemia was 24(15%) and anemia was 158(98%). Conclusion: Our study concludes that the frequency of biochemical profile of children were hyponatremia was 14%, hypokalemia was 68%, hypochloremia was 16%, hypoalbuminemia was 7%, hypocalcemia was 35, hypoglycemia was 15% and anemia was 98% with SAM presenting to Lady Reading Hospital, Peshawar.